The Other: Exploring the Life of An Intersex Individual in A Stigmatizing and Discriminating Society - Carissa Adelia Novinna (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
This creative thesis aims at showing the effects of stigma and discrimination on intersex individuals and how they can lessen the effects of stigma and discrimination through the medium of a screenplay titled The Other. I apply the theory of stigma as the main foundation of the creative work and the theory of self-acceptance as the resolution.  Utilizing the genre drama and the conventions of modern youth films, I employ the main character’s suffering and contentment accordingly to highlight the detrimental consequences of stigma and the psychological gain of self-acceptance. The Other follows Alexander Wijaya, then 16 years old, a boy who embarks on a self-discovery journey after discovering his intersexuality. As he faces bullying and other grievances, Alex begins to have self-doubt and feel ashamed and isolated. Later, Alex realizes his worth and retrieves back his confidence after he decides to accept his body the way it is.Keywords: Intersex, Stigma, Discrimination, Self-acceptance.